Edukasi Pertolongan Pertama Pada Keracunan Makanan Di SMK NU Pare - Laili, Nurul; Ishariani, Linda; Heni, Sutiyah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Abstract   Introduction: Food poisoning can cause complaints of dizziness, nausea, vomiting, diarrhea and even severe symptoms that can cause death. Signs and symptoms of food poisoning vary depending on the ingredients and amount of food consumed. Early recognition of signs and symptoms is needed for fast and appropriate treatment. Objective: The purpose of this service was provide insight and understanding about the management of food poisoning, especially in the school environment Method: The method of implementing activities is through education. The activity was carried out for 2 days on 29 – 30 September 2023 at SMK NU Pare. Participants are students of SMK NU Pare. Participants 29 people. Result: The results of the evaluation before being given education showed that almost half of the respondents with a percentage of 48.3% had the criteria for lacking knowledge, as many as 14 teenagers. The results of the evaluation after being provided with education showed that almost all respondents with a percentage of 86.2% had good knowledge criteria regarding first aid for food poisoning. Conclusion: Knowledge about handling food poisoning will influence attitudes and concern to be ready to anticipate food poisoning. Food poisoning emergencies can be handled immediately if you are prepared to deal with food poisoning incidents because you already know how to properly handle food poisoning.